2023
DOI: 10.1038/s41467-023-38235-9
|View full text |Cite
|
Sign up to set email alerts
|

Surface plasmon-enhanced photo-driven CO2 hydrogenation by hydroxy-terminated nickel nitride nanosheets

Abstract: The majority of visible light-active plasmonic catalysts are often limited to Au, Ag, Cu, Al, etc., which have considerations in terms of costs, accessibility, and instability. Here, we show hydroxy-terminated nickel nitride (Ni3N) nanosheets as an alternative to these metals. The Ni3N nanosheets catalyze CO2 hydrogenation with a high CO production rate (1212 mmol g−1 h−1) and selectivity (99%) using visible light. Reaction rate shows super-linear power law dependence on the light intensity, while quantum effi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(21 citation statements)
references
References 64 publications
1
18
0
Order By: Relevance
“…However, this mechanism relies upon particle clustering, and another study found that catalysts with commonly used low mass loadings (<5%) have too low a particle density to support a significant degree of cluster formation . Research supporting multielectron transfer mechanisms through the use of rapid multihole scavengers provided more evidence for a multicarrier transfer mechanism, and multitransfer mechanisms remain a popular explanation for the frequently observed superlinear relationship. , Alternatively, single-electron transfer mechanisms could still play a role in superlinear response by linearly affecting the concentration of a higher-order absorbate. Plasmonic nonthermal desorption has been shown to significantly affect reaction selectivity and rate. , If an intermediate, such as adsorbed hydrogen, has a sufficiently negative reaction order for the subsequent step rate-determining step, accelerating its desorption may contribute to a superlinear nonthermal rate dependence on intensity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, this mechanism relies upon particle clustering, and another study found that catalysts with commonly used low mass loadings (<5%) have too low a particle density to support a significant degree of cluster formation . Research supporting multielectron transfer mechanisms through the use of rapid multihole scavengers provided more evidence for a multicarrier transfer mechanism, and multitransfer mechanisms remain a popular explanation for the frequently observed superlinear relationship. , Alternatively, single-electron transfer mechanisms could still play a role in superlinear response by linearly affecting the concentration of a higher-order absorbate. Plasmonic nonthermal desorption has been shown to significantly affect reaction selectivity and rate. , If an intermediate, such as adsorbed hydrogen, has a sufficiently negative reaction order for the subsequent step rate-determining step, accelerating its desorption may contribute to a superlinear nonthermal rate dependence on intensity.…”
Section: Discussionmentioning
confidence: 99%
“…49 Research supporting multielectron transfer mechanisms through the use of rapid multihole scavengers 50 provided more evidence for a multicarrier transfer mechanism, and multitransfer mechanisms remain a popular explanation for the frequently observed superlinear relationship. 50,51 Alternatively, single-electron transfer mechanisms could still play a role in superlinear response by linearly affecting the concentration of a higher-order absorbate. Plasmonic nonthermal desorption has been shown to significantly affect reaction selectivity 48 and rate.…”
Section: Recognition Of Nonthermal Effects In a Modelmentioning
confidence: 99%
“…170–176 Among them, photocatalytic hydrogenation has been regarded as an important strategy to convert solar energy into hydrogen energy and some key chemicals, involving three primary steps: light absorption, charge separation and transfer and subsequent catalytic hydrogenation. 22,23,177–180 However, the current systems still suffer from low conversion efficiency. The key scientific problem lies in how to design and develop highly efficient photocatalysts to improve the efficiency of each step and the whole process.…”
Section: Transfer Hydrogenation Using Formic Acid As a Hydrogen Sourcementioning
confidence: 99%
“…Given the increasing global CO 2 levels, plasmon chemistry offers a promising solution. Plasmonic structures have shown potential in boosting the photoreduction of CO 2 , 119,123,126,127 which is crucial for environmental cleanup and advancing green chemistry. In a new development, researchers have presented a plasmonic photocatalyst that blends a copper (Cu) nanoparticle ''antenna'' with individual atomic ruthenium (Ru) sites (Fig.…”
Section: Perspective Pccpmentioning
confidence: 99%